2006
DOI: 10.1590/s1519-566x2006000500009
|View full text |Cite
|
Sign up to set email alerts
|

Una nueva especie Mexicana de Dichotomius Hope (Coleoptera: Scarabaeidae) y clave para la identificación de las especies del grupo carolinus

Abstract: El género Dichotomius Hope, 1838 es un género americano con 148 especies, siendo más diverso en Sudamérica, con cerca de cien especies. A la fecha el estado taxonómico del grupo es aun confuso y es necesaria una revisión (Medina et al. 2001, Kohlmann 2003). En México se localizan cinco especies (Kohlmann 2003), D amplicollis Harold, D. annae Kohlmann & Solís, D. colonicus (Say), D. satanas Harold y D. yucatanus Bates. El grupo carolinus se caracteriza por el ensanchamiento de la primera a la quinta estría elit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Although other authors have suggested larger distances for pitfall trapping, we set this distance as we are not using traps as replicates, but as subsamples in order to complete the species set of each site. Traps were left open 144 h and were baited with fresh dung every 48 h. Beetles were identified to the species level using a local reference collection of Scarabaeidae, following taxonomic keys [63][64][65][66][67][68][69][70][71] and with the help of specialists (Fernando Escobar and Pablo Minor Montiel from the Instituto de Ecología, A.C., Xalapa, México). trait data.…”
Section: Methodsmentioning
confidence: 99%
“…Although other authors have suggested larger distances for pitfall trapping, we set this distance as we are not using traps as replicates, but as subsamples in order to complete the species set of each site. Traps were left open 144 h and were baited with fresh dung every 48 h. Beetles were identified to the species level using a local reference collection of Scarabaeidae, following taxonomic keys [63][64][65][66][67][68][69][70][71] and with the help of specialists (Fernando Escobar and Pablo Minor Montiel from the Instituto de Ecología, A.C., Xalapa, México). trait data.…”
Section: Methodsmentioning
confidence: 99%
“…During the handling of traps and samples, the necessary prophylactic measures were taken to avoid any type of contamination. To identify the specimens, we used the keys of (Medina and Lopera-Toro 2000, Genier and Kohlmann 2003, Peraza and Deloya 2006, Vaz-De-Mello et al 2011, Solis and Kohlmann 2013, Sarmiento-Garcés and Amat-García 2014. In addition, the specimens were also compared with those present in the CEUA and the Francisco Luis Gallego Entomological Museum of the National University of Colombia in Medellin (MEFLG).…”
Section: Sampling Methodsmentioning
confidence: 99%
“…Estos individuos son alimentados con una dieta estándar de acuerdo con sus hábitos de alimentación. Los escarabajos capturados se transportaron a laboratorio en frascos con etanol al 70% y se identificaron a nivel de especies usando bibliografía taxonómica [28][29][30][31][32][33][34][35][36][37][38].…”
Section: Muestreo E Identificaciónunclassified